Cernaan In Sacco Ransum Ternak Sapi yang Menggunakan Kulit Buah Jagung Amoniasi - Andayani, Jul (Fakultas Peternakan Universitas Jambi, 2009)
An experiment was conducted to evaluate an improvement of corn peel with ammoniation in sacco digestibility in cow ration. Measured parameters in the current experiment were, in sacco degradation of dry matter, organic matter and crude protein. This study was assigned into completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were ; R0 = 70% Forage (100% grass + 0% Corn Peel) + 30 % Concentrate, R1 = 70% Forage (75 % grass + 25% Corn Peel) + 30 % Concentrate, R2 = 70% Forage (50% grass + 50% Corn Peel) + 30 % Concentrate, R3 = 70%Forage (25% grass + 75% Corn Peel) + 30 % Concentrate, R4 = 70% Forage (0% grass + 100% Corn Peel) + 30 % Concentrate. Result of this study showed that the treatments were significantly (P<0,05) influence degradation of dry matter, organic matter and crude protein. The degradation after ammoniation significantly increased and were higher than that of without ammoniation. It is concluded that ammoniation with urea of corn peel could increase degradation and could be used asforage substitution in ration.